BOSHLANG‘ICH SINF ONA TILI DARSLARIDA O‘QUVCHILARNING O‘QISH FAOLIYATINI MODELLASHTIRISH (INTERNATIONAL SCIENTIFIC INNOVATION RESEARCH CONFERENCE, 2026)
This article examines the theoretical and methodological foundations of modeling students’ reading activity in mother tongue lessons in primary school. Modeling reading activity is interpreted as an important pedagogical process aimed at developing conscious, expressive, and meaningful reading skills. The study analyzes the structural components of reading activity, types of modeling, and the role of interactive methods and didactic tools. Taking into account the age and psychological characteristics of primary school students, the article substantiates the possibilities of developing learning motivation, independent thinking, and speech competencies through modeling reading activity. The research results contribute to improving the effectiveness of mother tongue teaching methodology in primary education.